2005
DOI: 10.1073/pnas.0505446102
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral antibiotic resistance in Mycobacterium tuberculosis

Abstract: Chemotherapeutic options to treat tuberculosis are severely restricted by the intrinsic resistance of Mycobacterium tuberculosis to the majority of clinically applied antibiotics. Such resistance is partially provided by the low permeability of their unique cell envelope. Here we describe a complementary system that coordinates resistance to drugs that have penetrated the envelope, allowing mycobacteria to tolerate diverse classes of antibiotics that inhibit cytoplasmic targets. This system depends on whiB7, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
342
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(355 citation statements)
references
References 40 publications
13
342
0
Order By: Relevance
“…They concluded that eis may contribute to the enhanced growth of the 210 strain in human macrophages. Morris et al (2005) have also recently demonstrated that eis is a component of the whiB7 regulon, whose expression is upregulated by exposure to sublethal concentrations of antibiotics or fatty acids such as would be encountered within the host macrophage during infection. These reports in conjunction with the data presented here point to a significant but not yet clearly defined role for eis in the pathogenesis of M. tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that eis may contribute to the enhanced growth of the 210 strain in human macrophages. Morris et al (2005) have also recently demonstrated that eis is a component of the whiB7 regulon, whose expression is upregulated by exposure to sublethal concentrations of antibiotics or fatty acids such as would be encountered within the host macrophage during infection. These reports in conjunction with the data presented here point to a significant but not yet clearly defined role for eis in the pathogenesis of M. tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite intensive focus on the primary drug-target interaction and its maladaptive consequences, knowledge of the endogenous mechanisms used by bacteria to resist antibiotic activity is incomplete and centred chiefly around mechanisms associated with the drug-target interaction, such as drug efflux pumps and antibiotic-and/or target-modifying enzymes 3 . However, growing evidence has implicated a broader range of physiologic factors [7][8][9][10]27 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has expanded the scope of physiologic factors associated with antibiotic resistance to include broader bacterial stress responses, such as the SOS DNA stress response, heatshock response and oxidative stress response, as well as changes in metabolic state and activity [7][8][9][10][11][12] . These antibiotic-induced responses then contribute functionally to resistance.…”
mentioning
confidence: 99%
“…30,31,47,48 A molecular phylogeny based on these hypersensitive to several antibiotics. 78 Transcriptional analysis of all whiB genes in M. tb showed differential expression patterns in response to different stress conditions. 79 For example, WhiB3 was shown to interact with SigA 77 and responds to oxygen and nitric oxide, and is important for regulation of carbon metabolism.…”
Section: Attenuation Of Bcg After 1924mentioning
confidence: 99%